2006
DOI: 10.1097/00001888-200602000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Indian Medical Students' Views on Immigration for Training and Practice

Abstract: While optimism about future medical careers in India is increasing, the interest of Indian medical students in training and subsequently practicing in the United States remains high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 10 publications
6
18
3
2
Order By: Relevance
“…Importantly, our findings reflect prior work indicating the role of economic and political stability,25 professional opportunities,26 poor work environment27 and sub-optimal workforce dynamics 28 29. This study expands the framework to include intended and unintended effects of workforce policies and the broader contexts within which migration decisions are made.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Importantly, our findings reflect prior work indicating the role of economic and political stability,25 professional opportunities,26 poor work environment27 and sub-optimal workforce dynamics 28 29. This study expands the framework to include intended and unintended effects of workforce policies and the broader contexts within which migration decisions are made.…”
Section: Discussionsupporting
confidence: 75%
“…Among health workers in the African diaspora, Clemens et al 25 report an inverse relationship between economic and political stability and physician migration. Evidence from India indicates that perceived greater professional opportunities drive many potential migrant physicians 26. Similarly, a survey in Pakistan indicated that low remuneration and poor training and work environment influenced potential migrant physicians 27.…”
Section: Introductionmentioning
confidence: 99%
“…10,[14][15][16][17][18] As for this study, other studies [7][8][9]28 reported that many students were not sure of their future area of specialization. In many other developing countries, the critical step in the migration of medical graduates is the moment when they decide to obtain specialized training: a frequent individual decision is to look for it abroad, 7,[28][29][30] leading to a subsequent decision to stay in the host country. 28 Reflecting the lack of specialist training in the country, students in Cape Verde would like to obtain specialized training abroad.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about the long-term impact of the migration of health professionals from developing countries have recently led to a focus on the next generation, both in Africa [8][9][10][11][12][13][14] and elsewhere [15][16][17][18][19][20]. Many countries invest substantial financial resources in the training of physicians and nurses.…”
Section: Introductionmentioning
confidence: 99%